Improved certificateless sequential multi-signature scheme - Hong-zhen DU; Qiao-yan WEN (Tongxin xuebao)
A sequential multi-signature enabled multiple users to jointly sign a document in order.Xu,et al proposed a provably-secure certificateless sequential multi-signature scheme with constant signature length and pairing computations.However,it was shown that the scheme had a drawback in the verifying algorithm,and then it overcame the drawback.But,the efficiency of the corrected scheme was greatly reduced.An efficient certificateless sequential multi-signature scheme is constructed,and the multi-signature generated by proposed scheme consists of one group element and the verification algorithm requires only 2 bilinear pairings.